Student mastery activities to accompany How to design and evaluate research in education - Fraenkel, Jack R. (McGraw-Hill, 2006)
Student Mastery Activities Book The Student Mastery Activities book contains 100 activities that allow student to practice with key concepts explained in the text. The book is designed so it can be used for homework assignments or independent study.